Magnesium-based hydrogen-rich bone cement as well as preparation method and application thereof
Through the mixed curing of magnesium-based hydrogen-rich bone cement powder with the curing liquid and the low-temperature plasma surface activation treatment, the problems of poor binding performance and acidic environment in the human body are solved, and biocompatibility and mechanical strength are achieved. Improvement promotes bone tissue healing and regeneration.
Patent Information
- Application Number
- CN202411255840.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing magnesium-based bone cement has weak binding properties in the human body, which is prone to trigger local acidic environment and inflammatory reactions, and there are many organic residues on the surface, affecting biocompatibility and osteocyte proliferation.
Magnesium-based hydrogen-rich bone cement is used to cure by mixing powder with curing liquid, and low-temperature plasma surface activation treatment is applied to remove bonded consumables, improve surface roughness and hydrophilicity, and combine biodegradable polymers to embed magnesium-based materials as Healing promoter, adjust pH and reduce reaction calories.
It improves the biocompatibility and mechanical strength of bone cement, slows down the reaction speed of magnesium-based materials, prolongs the release time of hydrogen, inhibits inflammation, and promotes bone tissue healing and regeneration.
Smart Images

Figure CN119113229A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical bone cement, and in particular to a magnesium-based hydrogen-rich bone cement and a preparation method and application thereof. Background Art
[0002] Bones are important organs and tissues of the human body and also the supporting structure of the human body. Currently, the clinical treatments for bone repair include external fixation and surgical treatment. Bone cement is a new type of fracture fixation material with the advantages of easy operation, small usage, and stable performance. It can overcome the problems of external fixation and metal internal fixation surgery, such as complexity and heaviness.
[0003] Bone cement has a weak bonding performance with human tissue and produces acidic substances during the degradation process, which causes a decrease in the local pH of the implant area and easily causes inflammation of the surrounding tissues. Therefore, providing bone cement with good strength and biocompatibility, which can safely and stably promote natural bone ingrowth and remodeling, is an important direction of medical bone cement research.
[0004] In addition, during the preparation and application of bone cement ceramics, a certain amount of organic substances, such as binders, processing aids or degradation products of biomaterials, often remain on the surface. These organic residues may have an adverse effect on the performance and clinical effects of bone cement. Organic residues can affect the biocompatibility of bone cement ceramics. After implantation in the body, these organic substances may trigger a local inflammatory response, leading to tissue irritation in the implant area, delaying the healing process, and even causing early rejection of the implant.
[0005] Invention patent CN114767932B discloses a magnesium-based bone cement and a preparation method thereof, wherein the magnesium-based bone cement comprises magnesium-based bone cement powder, viscose-based carbon fiber and liquid, wherein the magnesium-based bone cement powder comprises magnesium oxide, calcium silicate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, boric acid, carboxymethyl cellulose and sucrose, and the total mass of magnesium-based bone cement powder and viscose-based carbon fiber is 100%, the mass of viscose-based carbon fiber accounts for 1% to 9%, and the mass of magnesium-based bone cement powder accounts for 91% to 99%. The invention treats the surface of viscose-based carbon fiber, grinds and mixes magnesium-based bone cement powder, and the magnesium-based bone cement has the advantages of high strength and toughness, easy preparation, etc., but does not pay attention to the surface properties of bone cement and the problem that it is easy to cause acidic environment and cause inflammation of surrounding tissues.
[0006] Invention CN112043862A discloses a magnesium sustained-release bone cement with self-curing function and its preparation method, the magnesium sustained-release bone cement is made by mixing and curing an aqueous solution and a powder, the powder includes the following raw material components by mass percentage: 60-95% calcium phosphate compound, 5-40% magnesium compound; the aqueous solution includes the following raw material components by mass percentage: 10-30% citric acid, 5-20% polyvinyl pyrrolidone, 40-84% deionized water. The surface activity of the bone cement is insufficient, the number of protein adsorption points in the human body is small, and there are more organic residues on the surface of the bone cement ceramic, which is not conducive to the proliferation and adhesion of bone cells, and it is easy to stimulate the surrounding tissues and induce inflammatory reactions.
[0007] Therefore, how to provide a magnesium-based bone cement that can alleviate local tissue inflammatory response, has strong antioxidant capacity and long antioxidant duration, has less organic residue on the surface of bone cement ceramics, has good biocompatibility and has sufficient mechanical strength is an urgent problem to be solved by technical personnel in this field. Summary of the invention
[0008] In view of the defects existing in the above-mentioned prior art, the present invention provides a magnesium-based hydrogen-rich bone cement and a preparation method and application thereof. By using components such as a magnesium-based healing promoter and surface activation treatment and other means, the magnesium-based hydrogen-rich bone cement can alleviate local tissue inflammatory response, has strong antioxidant ability and long antioxidant duration, has less organic residue on the surface of bone cement ceramics, has high surface activity and good biocompatibility.
[0009] In a first aspect, the present invention provides a magnesium-based hydrogen-rich bone cement, wherein the magnesium-based hydrogen-rich bone cement is prepared by mixing and curing a powder with a curing liquid;
[0010] The powder comprises the following components in parts by mass:
[0011]
[0012] The structural powder includes reinforcing powder and compatible powder, the reinforcing powder includes at least one of calcium silicate and calcium phosphate, and the compatible powder includes at least one of magnesium silicate and magnesium phosphate;
[0013] The mass ratio of the reinforcing powder to the compatible powder is (20-30):(30-50);
[0014] The healing promoter includes a biodegradable polymer and a magnesium-based material embedded in the biodegradable polymer;
[0015] After the powder and the curing liquid are mixed and cured, a surface activation treatment is applied and at least part of the bonding consumables is removed.
[0016] Magnesium-based hydrogen-rich bone cement has good mechanical strength, biocompatibility and bone regeneration ability, and can promote natural bone ingrowth and remodeling. The composite material containing magnesium-compatible powder has a bactericidal effect both in vitro and in vivo. As a bone substitute, the composite material can not only promote bone regeneration, but also prevent orthopedic implant infection to a certain extent; the bone cement containing calcium-enhanced powder has fast curing and high strength. The present invention adopts a combination of enhanced powder and compatible powder to ensure the biocompatibility and affinity of the material to bone tissue while providing strength. The optimization of the mass ratio between the two types of powders also helps to achieve a balance between strength and degradation rate. In addition, the healing promoter obtained by embedding magnesium-based materials with biodegradable polymers can slow down the reaction rate of magnesium-based materials, avoid emphysema, and react at the required speed to release hydrogen for a long time and stably, inhibit bacteria, slow down oxidative stress reactions, and help eliminate inflammation and promote wound healing.
[0017] After the powder and the curing liquid are mixed and cured, a surface activation treatment is applied, and at least part of the bonding consumables are removed. Through the surface activation treatment, undesirable residues can be effectively removed, and the surface roughness of the bone cement is improved, and the water contact angle is reduced, which is conducive to improving the binding performance of the bone cement and human tissue and the adhesion and proliferation of bone cells. The surface treatment basically does not introduce new substances and does not change the main properties of the material, so it basically does not cause the strength of the bone cement to decrease, and has long-term biosafety.
[0018] Preferably, the auxiliary agent comprises a stabilizer, a retarder and a cooling agent in a mass ratio of (10-20): (0.1-10): (5-10);
[0019] A stabilizer, including at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, calcium dihydrogen phosphate, and ammonium dihydrogen phosphate;
[0020] A retarder, including at least one of sucrose and glucose;
[0021] The cooling agent includes at least one of aluminum nitrate and magnesium nitrate.
[0022] The stabilizer reacts with the alkaline substances in the cement to generate potassium silicate and calcium silicate phosphate which are not easily soluble. During the curing process of bone cement, the local pH value can be adjusted, which helps to reduce the soluble alkali content in the bone cement, prevent the overly acidic or alkaline environment, protect the material and surrounding tissues, and thus reduce the risk of alkali-silicon reaction, improve the performance of bone cement and extend its service life. Secondly, phosphate ions are an essential component in the bone mineralization process. The addition of stabilizers can provide phosphate ions and promote the formation of hydroxyapatite, thereby improving the biological activity and bone inductivity of bone cement.
[0023] The retarder can slow down the excessively fast reaction speed of magnesium phosphate bone cement, reduce the reaction exothermic temperature, and thus increase the viscosity of the bone cement.
[0024] The cooling agent can absorb the heat generated when the bone cement is solidified, reduce the exothermic peak during the solidification process, and avoid thermal damage to surrounding tissues caused by excessive local temperature.
[0025] Preferably, the bonding consumables include at least one of polylactic acid-glycolic acid copolymer, polylactic acid, polyglycolic acid, polycaprolactone, poly-β-hydroxybutyric acid, polyhydroxyalkanoate, polylactic acid modified material, polycaprolactone modified material, and polylactic acid-glycolic acid copolymer modified material;
[0026] The surface activation treatment includes low-temperature plasma surface activation treatment. After the treatment, the surface roughness of the bone cement is increased by more than 10%, and the water contact angle is reduced by more than 75%.
[0027] Cold atmospheric plasma (CAP) is used as an emerging material surface modification method. It has low reaction temperature, high efficiency, and does not change the main properties of the material. When the bone cement surface is treated with cold atmospheric plasma, the microscopic morphology of the ceramic matrix does not change, and the resin embedded in the ceramic matrix is eroded by the cold plasma, thereby generating micron-level defects on the surface of the ceramic matrix. The defects can increase the specific surface area of the bone cement, and the material surface has more protein adsorption points, which is conducive to the adhesion and proliferation of osteoblasts. And this method can effectively remove organic residues on the surface of bone cement ceramics, promote surface chemical recombination, and reduce the viability of bacteria. Specifically, the surface roughness is increased and the water contact angle is reduced. The increased roughness provides more physical anchor points for cell adhesion, improves the interface bonding between the material and the biological tissue, and helps the attachment and proliferation of cells, thereby promoting the regeneration and healing of bone tissue. The surface roughness of bone cement increases by more than 10%, preferably by more than 15%, and the water contact angle decreases by more than 75%, preferably by more than 80%, and more preferably by more than 85%, indicating that the surface of bone cement changes from hydrophobic to highly hydrophilic after surface activation treatment. This significant increase in hydrophilicity helps to better interact with surrounding tissues and body fluids in a humid environment, enhance the biocompatibility of the material, and accelerate the tissue healing process.
[0028] Preferably, the solidifying liquid comprises at least one of a sodium chloride solution and a magnesium chloride solution, with a mass fraction of 0.5-1wt%, and a volume mass ratio of the solidifying liquid to the powder is (0.2-1) mL:1 g.
[0029] The sodium chloride solution / magnesium chloride solution with a mass fraction of 0.5-1wt% can realize the transformation of bone cement powder into ceramics, thereby improving the strength and wear resistance of the bone cement base. The ratio of the solidifying liquid and the powder can be adjusted within the above range according to the viscosity requirements.
[0030] Preferably, in the healing promoter, the mass ratio of the biodegradable polymer to the magnesium-based material is (95-99): (1-5);
[0031] The magnesium-based material includes at least one of magnesium and magnesium hydride;
[0032] The biodegradable polymer comprises poly(lactic-co-glycolic acid);
[0033] The healing accelerator is prepared by the following steps:
[0034] S1, dissolving polylactic acid-co-glycolic acid and polyethylene glycol in an organic solvent, and adding a magnesium-based material to obtain a mixed solution;
[0035] S2, volatilizing the organic solvent in the mixed solution, centrifuging, and drying the precipitate to obtain a healing promoter of polylactic acid-glycolic acid copolymer-embedded magnesium-based material.
[0036] Polylactic acid-co-glycolic acid is a medical resin with good biocompatibility and biodegradability. The magnesium-based material treated by polylactic acid-co-glycolic acid embedding technology, preferably magnesium hydride, can release hydrogen at a reasonable rate and for a long time in the body fluid environment, thereby effectively avoiding emphysema caused by excessive H2 production. Thereby achieving the effect of inhibiting bacteria, slowing down oxidative stress response, eliminating inflammatory symptoms, and promoting wound healing.
[0037] Optionally, after the powder is mixed with the curing liquid and cured to obtain the magnesium-based hydrogen-rich bone cement, part of the biodegradable polymer is removed. When the healing promoter is located on the surface of the bone cement, after the low-temperature plasma activation treatment, part of the polymer will be removed, and the magnesium-based material will be more likely to participate in the initial reaction, while the healing promoter inside the bone cement will not be affected and will slowly release hydrogen later.
[0038] Preferably, the organic solvent is at least one of 1-,4-dioxane, dimethyl sulfoxide, chloroform and dichloromethane, preferably dimethyl sulfoxide. The amount ratio of polylactic acid-co-glycolic acid, polyethylene glycol, organic solvent (preferably dimethyl sulfoxide) and magnesium-based material (preferably magnesium hydride) is (8-20) mg: (1-3) mg: (0.8-1.5) mL: (0.1-1) mg.
[0039] In a second aspect, the present invention also provides a method for preparing the magnesium-based hydrogen-rich bone cement, comprising the following steps:
[0040] Step 1: Mix the structural powder, bonding consumables, healing promoter and additives in proportion to obtain powder;
[0041] Step 2: Mix the powder and the solidifying liquid and transform them into a paste;
[0042] Step 3, applying the paste and curing it into magnesium-based hydrogen-rich bone cement;
[0043] Step 4: Applying surface activation treatment to the solidified magnesium-based hydrogen-rich bone cement, at least part of the bonding consumables is removed.
[0044] Preferably, in step 4, the surface activation treatment adopts low-temperature plasma surface activation treatment, comprising the following steps:
[0045] S1, introducing working gas, and using high-frequency and high-voltage current to ionize the working gas to generate low-temperature plasma;
[0046] S2, low-temperature plasma impacts the surface of bone cement, at least part of the bonding consumables is removed, and nano-scale grooves are formed on the surface of bone cement;
[0047] S3. The removed bonding consumables are removed by suction from the surface of the bone cement.
[0048] Preferably, the low-temperature plasma surface activation treatment uses a low-temperature plasma activator, and the low-temperature plasma activator includes a plasma gun;
[0049] The plasma gun includes a muzzle sleeve, an electrode blowpipe and a gun seat;
[0050] The muzzle sleeve has a coaxial inner wall and an outer wall, and a suction ring is formed between the inner wall and the outer wall. The muzzle sleeve is connected to the gun seat, and the suction ring is connected to a vacuum tube fixed on the gun seat.
[0051] The electrode blowpipe is arranged in the inner cavity of the muzzle sleeve and connected to the gun seat. The electrode blowpipe includes a blowpipe shell, a discharge cavity and an electrode arranged on the inner wall of the blowpipe shell. The electrode is connected to an electrode wire fixed on the gun seat, and the discharge cavity is connected to a working gas nozzle fixed on the gun seat.
[0052] Among them, the vacuum tube, electrode wire and working gas nozzle can be integrated in a composite cable and are respectively connected to a vacuum source, a power source and a working gas source. The low-temperature plasma activator also includes a controller, which is connected to the composite cable and regulates the working states of the vacuum tube, electrode wire and working gas nozzle.
[0053] The low-temperature plasma surface activator used in the present invention is a device specially used for bone cement surface treatment. Further, the muzzle sleeve has a coaxial inner wall and outer wall, the inner wall is shorter than the outer wall, that is, the inner wall is contained in the cavity surrounded by the outer wall, the outer wall end forms a tangent coil, the tangent coil can form a relatively sealed abutment with the target surface, the inner wall forms the inner cavity of the muzzle sleeve, the electrode blowpipe is arranged in the inner cavity, and a diffusion zone is formed between the outlet end of the electrode blowpipe and the inner wall end, when the low-temperature plasma generated by the electrode blowpipe is ejected from the outlet end of the electrode blowpipe and hits the bone cement surface, the fragments and gas generated by the bombardment are confined in the diffusion zone by the tangent coil, and are quickly sucked out by the suction ring between the inner wall and the outer wall.
[0054] Preferably, the low temperature plasma surface activation treatment conditions include:
[0055] Ar gas is used as the working gas, the working gas flow rate is 3.5-5.5 sp lm, the discharge frequency is 15.0-25.0 kHz, the discharge voltage is 1.5-3.5 kV to generate Ar plasma, the action distance is 5-15 mm, and the processing time is 90-150 s;
[0056] The speed at which the bonding consumables are removed by suction from the surface of the bone cement is greater than or equal to the speed at which the working gas is introduced.
[0057] The low-temperature plasma surface activator adopted in the present invention uses a vacuum tube to quickly extract the gas and splashed ceramic particles in the diffusion zone through a suction method slightly higher than the intake speed, thereby avoiding the ceramic particles from affecting the uniformity of the surface treatment during the surface treatment process, and preventing the particles from accumulating in the sleeve or diffusing into the external environment.
[0058] Accordingly, the low-temperature plasma surface activation treatment specifically includes the following steps:
[0059] (1) using a working gas nozzle to introduce Ar working gas into the discharge chamber, the working gas flow rate is 3.5-5.5 sp lm, the discharge frequency of the electrode on the inner wall of the blowpipe shell is 15.0-25.0 kHz, and the discharge voltage is 1.5-3.5 kV, so that the Ar working gas is ionized to generate low-temperature Ar plasma;
[0060] (2) low-temperature plasma impacts the surface of bone cement at a distance of 5-15 mm and a treatment time of 90-150 s, at least a portion of the bonding consumables is removed, and nanoscale grooves are formed on the surface of the bone cement;
[0061] (3) A vacuum tube is used to generate a vacuum in a suction ring between the inner and outer walls of the muzzle sleeve. The suction speed provided by the vacuum inside the suction ring is greater than the speed of introducing the Ar working gas. The preferred suction speed is above 4.5 sp lm, so that the adhesive consumables to be removed are quickly sucked out from the surface of the bone cement.
[0062] In a third aspect, the present invention provides a use of the magnesium-based hydrogen-rich bone cement in the preparation of bone defect repair materials.
[0063] The present invention has at least the following beneficial effects:
[0064] (1) The magnesium-based hydrogen-rich bone cement of the present invention uses a magnesium-based material coated with a biodegradable material as a healing promoter, which can slow down the reaction rate of magnesium-based materials such as magnesium hydride during the degradation of bone cement, achieve the slow release of hydrogen, and thus prolong the release time of hydrogen, ensure a continuous healing promotion effect, and avoid excessive release of hydrogen causing local gas accumulation or tissue irritation. The released hydrogen has antioxidant, anti-inflammatory and tissue healing promoting effects, which helps to reduce local inflammation after implantation and accelerate bone tissue repair.
[0065] (2) The present invention performs low-temperature plasma surface activation treatment on the solidified bone cement, which effectively improves the roughness and hydrophilicity of the bone cement surface, significantly enhances the interfacial adhesion between the material and the bone tissue, and this surface activation combined with the sustained release of magnesium hydride not only promotes the continuous release of hydrogen, but also further enhances the healing effect of magnesium-based bone cement. After removing the bonding consumables in the bone cement, sufficient interfacial adhesion and mechanical strength can still be maintained through surface activation treatment, thereby ensuring the overall performance and biocompatibility of the material.
[0066] (3) In view of the specific application of the magnesium-based hydrogen-rich bone cement of the present invention in the preparation of bone defect repair materials, a low-temperature plasma surface activator with a compact structure and high control precision is provided. In combination with the solidified magnesium-based hydrogen-rich bone cement, a low-temperature plasma surface activation treatment can be stably performed, and impurities such as removed adhesive consumables can be quickly removed by suction, thereby improving the surface activity and avoiding surface residues. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 It is a front view of the low-temperature plasma activator of the present invention;
[0068] Figure 2 is a side view of a plasma gun of the present invention;
[0069] Figure 3 It is a structural schematic diagram of a plasma gun of the present invention;
[0070] Figure 4 It is a working schematic diagram of the low-temperature plasma activator of the present invention.
[0071] Explanation of the reference numerals: 100 - low-temperature plasma activator, 1 - plasma gun, 11 - muzzle sleeve, 111 - outer wall, 112 - inner wall, 113 - suction ring, 114 - cutting coil, 115 - plasma nozzle, 12 - electrode blowpipe, 121 - blowpipe housing, 122 - discharge chamber, 123 - electrode, 13 - gun seat, 131 - vacuum tube, 1321, 1322 - electrode wire, 133 - working gas nozzle, 2 - composite cable, 3 - controller, 200 - bone cement surface. DETAILED DESCRIPTION
[0072] In order to better understand the above technical solution, the above technical solution will be described in detail below in combination with the specification and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0073] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.
[0074] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0075] The present invention provides a magnesium-based hydrogen-rich bone cement prepared by mixing and curing a powder and a curing liquid, comprising:
[0076] (1) Powder, calculated by weight, includes 50-80 parts of structural powder, 10-15 parts of bonding consumables, 5-10 parts of healing promoter, and 15-40 parts of auxiliary agent, wherein:
[0077] (1.1) structural powder, including reinforcing powder and compatible powder, the reinforcing powder includes at least one of calcium silicate and calcium phosphate, the compatible powder includes at least one of magnesium silicate and magnesium phosphate, and the mass ratio of the reinforcing powder to the compatible powder is (20-30): (30-50);
[0078] (1.2) Adhesive consumables, including at least one of polylactic acid-glycolic acid copolymer, polylactic acid, polyglycolic acid, polycaprolactone, poly-β-hydroxybutyric acid, polyhydroxyalkanoate, polylactic acid modified material, polycaprolactone modified material, and polylactic acid-glycolic acid copolymer modified material; after the powder and the curing liquid are mixed and cured, a surface activation treatment is applied, and at least part of the adhesive consumables is removed. After the treatment, the surface roughness of the bone cement can be increased by more than 10%, preferably more than 15%, and the water contact angle is reduced by more than 75%, preferably more than 80%, and more preferably more than 85%;
[0079] (1.3) a healing promoter, comprising a biodegradable polymer and a magnesium-based material embedded in the biodegradable polymer, wherein the mass ratio of the biodegradable polymer to the magnesium-based material is (95-99): (1-5);
[0080] The magnesium-based material comprises at least one of magnesium and magnesium hydride, preferably magnesium hydride, and the biodegradable polymer comprises polylactic acid-co-glycolic acid;
[0081] The healing accelerator is prepared by the following steps:
[0082] S1, dissolving polylactic acid-co-glycolic acid and polyethylene glycol (molecular weight 800-1000) in an organic solvent, adding a magnesium-based material to obtain a mixed solution;
[0083] S2, volatilizing the organic solvent in the mixed solution, centrifuging, and drying the precipitate to obtain a healing promoter of polylactic acid-glycolic acid copolymer-embedded magnesium-based material.
[0084] The organic solvent is at least one of 1-,4-dioxane, dimethyl sulfoxide, chloroform and dichloromethane, preferably dimethyl sulfoxide. The amount ratio of polylactic acid-glycolic acid copolymer, polyethylene glycol, organic solvent and magnesium-based material is (8-20) mg: (1-3) mg: (0.8-1.5) mL: (0.1-1) mg.
[0085] (1.4) additives, including stabilizers, retarders and cooling agents, wherein the mass ratio of stabilizers, retarders and cooling agents is (10-20): (0.1-10): (5-10);
[0086] A stabilizer, including at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, calcium dihydrogen phosphate, and ammonium dihydrogen phosphate;
[0087] A retarder, including at least one of sucrose and glucose;
[0088] The cooling agent includes at least one of aluminum nitrate and magnesium nitrate.
[0089] (2) The solidifying liquid comprises at least one of a sodium chloride solution and a magnesium chloride solution with a mass fraction of 0.5-1 wt%. The volume mass ratio of the solidifying liquid to the powder is (0.2-1) mL:1 g.
[0090] For the aforementioned magnesium-based hydrogen-rich bone cement, the preparation method provided by the present invention comprises the following steps:
[0091] Preparatory step: preparing the healing promoter, specifically by the following steps:
[0092] S1, dissolving polylactic acid-co-glycolic acid and polyethylene glycol (molecular weight 800-1000) in an organic solvent, adding a magnesium-based material to obtain a mixed solution;
[0093] S2, volatilizing the organic solvent in the mixed solution, centrifuging, and drying the precipitate to obtain a healing promoter of polylactic acid-glycolic acid copolymer-embedded magnesium-based material.
[0094] Step 1: Mix the structural powder, bonding consumables, healing promoter and additives in proportion to obtain powder;
[0095] Step 2: Mix the powder and the solidifying liquid with a mixing hose, connect the mixing hose to the powder bag and the solidifying liquid bag, and repeatedly pump and stir to convert into a paste;
[0096] Step 3, applying the paste and curing it into magnesium-based hydrogen-rich bone cement;
[0097] Step 4: Applying surface activation treatment to the solidified magnesium-based hydrogen-rich bone cement, at least part of the bonding consumables is removed.
[0098] Preferably, in step four, the surface activation treatment adopts low-temperature plasma surface activation treatment, using Ar gas as the working gas, the working gas flow rate is 3.5-5.5sp lm, the discharge frequency is 15.0-25.0kHz, the discharge voltage is 1.5-3.5kV to generate Ar plasma, the action distance is 5-15mm, and the treatment time is 90-150s; and the speed at which the bonding consumables are sucked away from the surface of the bone cement is greater than the speed at which the Ar working gas is introduced.
[0099] See attached Figure 1-4 , in response to the needs of the bone cement surface 200 and the repair scene, the present invention adopts a low-temperature plasma activator 100 in the low-temperature plasma surface activation treatment, including a plasma gun 1, a composite cable 2 and a controller 3;
[0100] The plasma gun 1 comprises a muzzle sleeve 11, an electrode blowpipe 12 and a gun base 13;
[0101] The muzzle sleeve 11 has a coaxial outer wall 111 and an inner wall 112, and a suction ring 113 formed between the inner wall 112 and the outer wall 111. The muzzle sleeve 11 is connected to the gun base 13, and the suction ring 113 is connected to a vacuum tube 131 fixed on the gun base 13;
[0102] The electrode blowpipe 12 is arranged in the inner cavity of the muzzle sleeve 11 and connected to the gun seat 13. The electrode blowpipe 12 includes a blowpipe shell 121, a discharge cavity 122 and an electrode 123 arranged on the inner wall of the blowpipe shell 121. The electrode 123 is connected to the electrode wire (1321, 1322) fixed on the gun seat 13 through the electrode plug, and the discharge cavity 122 is connected to the working gas nozzle 133 fixed on the gun seat 13.
[0103] Among them, the length of the inner wall 112 of the muzzle sleeve 11 is shorter than the length of the outer wall 111, that is, the inner wall 112 is received in the cavity surrounded by the outer wall 111, and a cutting coil 114 is formed at the end of the outer wall 111. The cutting coil 114 surrounds an outward plasma nozzle 115, and the cutting coil 114 can form a relatively sealed abutment with the target surface. The inner wall 112 forms an inner cavity of the muzzle sleeve 11, and the electrode blowpipe 12 is arranged in the inner cavity, and a diffusion zone is formed between the outlet end of the electrode blowpipe 12 and the end of the inner wall 112. When the low-temperature plasma generated by the electrode blowpipe 12 is ejected from the outlet end of the electrode blowpipe 12, ejected along the plasma nozzle 115 and hits the bone cement surface 200, the fragments and gases generated by the bombardment are confined in the diffusion zone by the cutting coil 114, and are quickly sucked away by the suction ring 113 between the inner wall 112 and the outer wall 111.
[0104] The composite cable 2, the vacuum tube 131, the electrode wires (1321, 1322) and the working gas nozzle 133 are integrated in the composite cable 2, and are respectively connected to a vacuum source, a power source and a working gas source (not shown);
[0105] The controller 3 is connected to the composite line 2 and regulates the working states of the vacuum tube 131 , the electrode lines ( 1321 , 1322 ) and the working gas nozzle 133 .
[0106] Low-temperature plasma surface activation treatment specifically includes the following steps:
[0107] S5.1, using Ar plasma as the working gas, the working gas flow rate is 3.5-5.5sp lm, the discharge frequency is 15.0-25.0kHz, the discharge voltage is 1.5-3.5kV, and the distance is 5-15mm to generate low-temperature plasma;
[0108] S5.2, low-temperature plasma impacts the surface of bone cement for 90-150 seconds, at least part of the bonding consumables is removed, and nano-scale grooves are formed on the surface of bone cement;
[0109] S5.3. The removed bonding consumables are removed by suction from the surface of the bone cement. The speed of suction from the surface of the bone cement is greater than the speed of introducing the working gas. Preferably, the suction speed is above 4.5 sp lm.
[0110] Existing low-temperature plasma equipment, due to differences in application objects and scenarios, usually adopts an open mouthpiece, which is only responsible for blowing ionized gas from the electrode to generate cold plasma, but after surface treatment, the splashing direction of the gas and possible products is not controllable, and it is easy to cause the problem of surface contamination after treatment. The present invention is directed to the surface of solidified bone cement, and the low-temperature plasma activator and its implementation method, in addition to generating a cold plasma flame, is also provided with a suction ring for suction to capture splashing materials and residual gas, which can better meet the requirements for cleaning and sterilization of the treated surface. In addition, the low-temperature plasma activator has a simple structure, is easy to assemble, has a compact inlet and outlet design, and is convenient and stable to operate.
[0111] After the aforementioned low-temperature plasma surface activation treatment, the surface roughness of the bone cement increases by more than 10%, preferably by more than 15%, and the water contact angle decreases by more than 75%, preferably by more than 80%, and more preferably by more than 85%. The surface treatment of the bone cement material by low-temperature plasma is at the micro-nano level and will not affect the strength of the bone cement material itself.
[0112] In addition, the cell MC3T3-E1 cells were inoculated on the surface of the magnesium-based hydrogen-rich bone cement of the present invention, and cultured in a constant temperature incubator at 37°C, 5% CO2 and 95% saturated humidity. After 7 days of culture, the cell ALP expression was tested by the pNPP method. After treatment, the cell ALP expression increased by more than 2 times. It can be seen that the magnesium-based hydrogen-rich bone cement treated with surfactant safely and efficiently improves the surface roughness of the bone cement and reduces the water contact angle to form a highly bioactive and compatible surface. The healing-promoting effect of the slow release of hydrogen by the magnesium-based material can effectively eliminate inflammation and promote repair and wound healing.
[0113] Example 1
[0114] The magnesium-based hydrogen-rich bone cement provided in this embodiment is prepared by mixing powder and curing liquid and curing, and its raw material components include:
[0115] (1) Powders, in parts by mass, comprising:
[0116] (1.1) 65 parts of structural powder, specifically including 25 parts of calcium silicate (reinforcement powder) and 40 parts of magnesium phosphate (compatible powder);
[0117] (1.2) 10 parts of bonding consumables, including polylactic acid-glycolic acid copolymer;
[0118] (1.3) 9 parts of a healing promoter, comprising magnesium hydride embedded in polylactic acid-co-glycolic acid copolymer, wherein the mass ratio of polylactic acid-co-glycolic acid copolymer to magnesium hydride is 95:5;
[0119] (1.4) 16 parts of auxiliary agents, including 10 parts of potassium dihydrogen phosphate (stabilizer), 1 part of glucose (retardant), and 5 parts of aluminum nitrate (cooling agent);
[0120] (2) A solidifying liquid, comprising a sodium chloride solution with a mass fraction of 1 wt %, and a volume mass ratio of the solidifying liquid to the powder is 0.5 mL:1 g.
[0121] The preparation method of the magnesium-based hydrogen-rich bone cement sample 1 corresponding to Example 1 includes:
[0122] The preliminary step is to prepare the healing promoter, which is specifically prepared by the following steps:
[0123] (1) dissolving poly(lactic acid-co-glycolic acid) and polyethylene glycol 1000 in dimethyl sulfoxide, and adding magnesium hydride to obtain a mixed solution;
[0124] (2) volatilizing the organic solvent in the mixed solution, centrifuging, and drying the precipitate to obtain a healing promoter of polylactic acid-glycolic acid copolymer-embedded magnesium hydride.
[0125] The usage ratio of polylactic acid-glycolic acid copolymer, polyethylene glycol, dimethyl sulfoxide and magnesium hydride is about 11.4 mg: 2 mg: 1 mL: 0.6 mg.
[0126] Step 1: Mix the structural powder, bonding consumables, healing promoter and additives in proportion to obtain powder;
[0127] Step 2: Mix the powder and the solidifying liquid with a mixing hose, connect the mixing hose to the powder bag and the solidifying liquid bag, and repeatedly pump and stir to convert into a paste;
[0128] Step 3: Apply the paste and cure it naturally at room temperature to form magnesium-based hydrogen-rich bone cement;
[0129] Step 4: Using a low-temperature plasma activator 100 to perform low-temperature plasma surface activation treatment on the solidified magnesium-based hydrogen-rich bone cement, comprising:
[0130] S4.1, using Ar gas as the working gas, the working gas flow rate is about 4.27sp lm, the discharge frequency is 17kHz, the discharge voltage is 2.62kV to generate low-temperature Ar plasma, and the action distance is about 10±1mm;
[0131] S5.2, the low-temperature plasma impacts the surface of the bone cement for 120 seconds, at least part of the bonding consumables is removed, and nano-scale grooves are formed on the surface of the bone cement;
[0132] S5.3. The removed bonding consumables are removed by suction from the surface of the bone cement. The speed of suction removal of the bonding consumables from the surface of the bone cement is about 4.6 sp lm, which is greater than the speed of introducing the working gas.
[0133] Example 2
[0134] The magnesium-based hydrogen-rich bone cement provided in this embodiment is different from the sample in Example 1 mainly in that the proportion of raw material components is different, and the raw material components include:
[0135] (1) Powders, in parts by mass, comprising:
[0136] (1.1) 50 parts of structural powder, specifically including 20 parts of calcium silicate (reinforcement powder) and 30 parts of magnesium phosphate (compatible powder);
[0137] (1.2) 15 parts of bonding consumables, including polylactic acid-glycolic acid copolymer;
[0138] (1.3) 10 parts of a healing promoter, comprising magnesium hydride embedded in polylactic acid-co-glycolic acid copolymer, wherein the mass ratio of polylactic acid-co-glycolic acid copolymer to magnesium hydride is 95:5;
[0139] (1.4) 25 parts of auxiliary agents, including 15 parts of potassium dihydrogen phosphate (stabilizer), 3 parts of glucose (retardant), and 7 parts of aluminum nitrate (cooling agent);
[0140] (2) A solidifying liquid, comprising a sodium chloride solution with a mass fraction of 1 wt %, and a volume mass ratio of the solidifying liquid to the powder is 0.5 mL:1 g.
[0141] According to the above ratio, the same magnesium-based hydrogen-rich bone cement preparation method as Example 1 was adopted to obtain Sample 2.
[0142] Example 3
[0143] The magnesium-based hydrogen-rich bone cement provided in this embodiment is different from the sample in Example 1 mainly in that the proportion of raw material components is different, and the raw material components include:
[0144] (1) Powders, in parts by mass, comprising:
[0145] (1.1) 80 parts of structural powder, specifically including 30 parts of calcium silicate (reinforcement powder) and 50 parts of magnesium phosphate (compatible powder);
[0146] (1.2) 10 parts of bonding consumables, including polylactic acid-glycolic acid copolymer;
[0147] (1.3) 9 parts of a healing promoter, comprising magnesium hydride embedded in polylactic acid-co-glycolic acid copolymer, wherein the mass ratio of polylactic acid-co-glycolic acid copolymer to magnesium hydride is 95:5;
[0148] (1.4) 16 parts of auxiliary agents, including 10 parts of potassium dihydrogen phosphate (stabilizer), 1 part of glucose (retardant), and 5 parts of aluminum nitrate (cooling agent);
[0149] (2) A solidifying liquid, comprising a sodium chloride solution with a mass fraction of 1 wt %, and a volume mass ratio of the solidifying liquid to the powder is 0.5 mL:1 g.
[0150] According to the above ratio, sample 3 was obtained by adopting the same magnesium-based hydrogen-rich bone cement preparation method as Example 1.
[0151] Comparative Example 1
[0152] Sample D1 of Comparative Example 1 adopts the same bone cement component formula and substantially the same preparation method as Example 1, but does not undergo surface activation treatment.
[0153] Comparative Example 2
[0154] The bone cement components of sample D2 of comparative example 2 differ from those of example 1 in that only 6 parts of bonding consumables are used, and the remaining components and preparation methods are the same.
[0155] Comparative Example 3
[0156] The bone cement components of sample D3 of comparative example 3 differ from those of example 1 in that no healing promoter is used, and the remaining components and preparation methods are the same.
[0157] Test Method
[0158] The following tests were performed on samples 1-3 of the embodiment and samples D1-3 of the comparative example:
[0159] (1) Surface roughness: Three test points were randomly selected within the center of each sample, and the arithmetic mean deviation (Ra value) of the profile was measured using a portable roughness meter. The average value was calculated as the surface roughness of the specimen. The measuring length of the portable roughness meter was 4 mm and the sampling length was 0.8 mm.
[0160] (2) Water contact angle: Three test points were randomly selected within the center of each sample, and the water contact angle was measured using a video optical contact angle meter by static contact angle measurement.
[0161] (3) Cell ALP expression test: MC3T3-E1 cells were inoculated on the surface of hydrogen-rich bone cement and cultured in a constant temperature incubator at 37°C, 5% CO2 and 95% saturated humidity. After 7 days of culture, the cell ALP expression was tested using the pNPP method.
[0162] (4) Mechanical properties test: The compressive strength of the samples was tested using an electronic universal testing machine with a loading rate of 0.5 mm / min. Each component sample was tested three times and the average value was calculated.
[0163] The composition and properties of samples 1-3 and sample D1-3 are shown in Table 1:
[0164] Table 1:
[0165]
[0166]
[0167]
[0168] It can be seen from the test results that the surface roughness of Example samples 1-3 is above 0.10 μm, the water contact angle is less than 10.0°, the cell ALP expression is above 30, and the compressive strength is maintained above 30 MPa. Compared with the comparative sample D1 without surface treatment, the surface roughness, water contact angle, and cell ALP expression are improved. Compared with the sample 1 after surface treatment, the compressive strength is not much reduced. It can be seen that the implementation of surface active treatment is generally beneficial to the improvement of bone cement surface activity and biocompatibility, and increases the ability of osteoblasts and surrounding tissues to grow, but does not basically affect the demand for bone cement repair strength. In addition to the good surface properties of samples 2 and 3, the difference in compressive strength is relatively obvious due to the difference in the content of the structural powder. Therefore, in practical applications, the strength requirements of bone cement in different parts can be met by adjusting the component content.
[0169] Since comparative sample D2 uses less bonding consumables and sample D3 does not use a healing promoter, the comprehensive performance of the two in terms of surface activity and biological properties is not as good as that of the embodiments, which also reflects the positive improvement effect and effect of using an appropriate amount of bonding consumables and healing promoters in the present invention.
[0170] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concepts. Therefore, the present invention is intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention.
Claims
1. A magnesium-based hydrogen-rich bone cement, characterized in that: The magnesium-based hydrogen-rich bone cement is prepared by mixing a powder and a curing liquid and curing them; The powder comprises the following components in parts by mass: The structural powder includes reinforcing powder and compatible powder, the reinforcing powder includes at least one of calcium silicate and calcium phosphate, and the compatible powder includes at least one of magnesium silicate and magnesium phosphate; The mass ratio of the reinforcing powder to the compatible powder is (20-30):(30-50); The healing promoter includes a biodegradable polymer and a magnesium-based material embedded in the biodegradable polymer; After the powder and the curing liquid are mixed and cured, a surface activation treatment is applied and at least part of the bonding consumables is removed.
2. The magnesium-based hydrogen-rich bone cement according to claim 1, characterized in that: The auxiliary agent includes a stabilizer, a retarder and a cooling agent in a mass ratio of (10-20): (0.1-10): (5-10); A stabilizer, including at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, calcium dihydrogen phosphate, and ammonium dihydrogen phosphate; A retarder, including at least one of sucrose and glucose; The cooling agent includes at least one of aluminum nitrate and magnesium nitrate.
3. The magnesium-based hydrogen-rich bone cement according to claim 1, characterized in that: The bonding consumables include at least one of polylactic acid-glycolic acid copolymer, polylactic acid, polyglycolic acid, polycaprolactone, poly-β-hydroxybutyric acid, polyhydroxyalkanoate, polylactic acid modified material, polycaprolactone modified material, and polylactic acid-glycolic acid copolymer modified material; The surface activation treatment adopts low-temperature plasma surface activation treatment. After the treatment, the surface roughness of the bone cement is increased by more than 10% and the water contact angle is reduced by more than 75%.
4. The magnesium-based hydrogen-rich bone cement according to any one of claims 1 to 3, characterized in that: The solidifying liquid comprises at least one of a sodium chloride solution and a magnesium chloride solution, with a mass fraction of 0.5-1wt%, and a volume mass ratio of the solidifying liquid to the powder is (0.2-1) mL:1g.
5. The magnesium-based hydrogen-rich bone cement according to claim 4, characterized in that: In the healing promoter, the mass ratio of the biodegradable polymer to the magnesium-based material is (95-99):(1-5); The magnesium-based material includes at least one of magnesium and magnesium hydride; The biodegradable polymer comprises poly(lactic-co-glycolic acid); The healing accelerator is prepared by the following steps: S1, dissolving polylactic acid-co-glycolic acid and polyethylene glycol in an organic solvent, and adding a magnesium-based material to obtain a mixed solution; S2, volatilizing the organic solvent in the mixed solution, centrifuging, and drying the precipitate to obtain a healing promoter of polylactic acid-glycolic acid copolymer-embedded magnesium-based material.
6. A method for preparing the magnesium-based hydrogen-rich bone cement according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Mix the structural powder, bonding consumables, healing promoter and additives in proportion to obtain powder; Step 2: Mix the powder and the solidifying liquid and transform them into a paste; Step 3, applying the paste and curing it into magnesium-based hydrogen-rich bone cement; Step 4: Applying surface activation treatment to the solidified magnesium-based hydrogen-rich bone cement, at least part of the bonding consumables is removed.
7. The preparation method according to claim 6, characterized in that: In step 4, the surface activation treatment adopts low-temperature plasma surface activation treatment, which includes the following steps: S1, introducing working gas, and using high-frequency and high-voltage current to ionize the working gas to generate low-temperature plasma; S2, low-temperature plasma impacts the surface of bone cement, at least part of the bonding consumables is removed, and nano-scale grooves are formed on the surface of bone cement; S3. The removed bonding consumables are removed by suction from the surface of the bone cement.
8. The preparation method according to claim 7, characterized in that: Low-temperature plasma surface activation treatment uses a low-temperature plasma activator, including a plasma gun; The plasma gun includes a muzzle sleeve, an electrode blowpipe and a gun seat; The muzzle sleeve has a coaxial inner wall and an outer wall, and a suction ring is formed between the inner wall and the outer wall. The muzzle sleeve is connected to the gun seat, and the suction ring is connected to a vacuum tube fixed on the gun seat. The electrode blowpipe is arranged in the inner cavity of the muzzle sleeve and connected to the gun seat. The electrode blowpipe includes a blowpipe shell, a discharge cavity and an electrode arranged on the inner wall of the blowpipe shell. The electrode is connected to an electrode wire fixed on the gun seat, and the discharge cavity is connected to a working gas nozzle fixed on the gun seat.
9. The preparation method according to claim 7 or 8, characterized in that: Low temperature plasma surface activation treatment conditions include: Ar gas is used as the working gas, the working gas flow rate is 3.5-5.5 splm, the discharge frequency is 15.0-25.0 kHz, the discharge voltage is 1.5-3.5 kV to generate Ar plasma, the action distance is 5-15 mm, and the processing time is 90-150 s; The speed at which the bonding consumables are removed by suction from the surface of the bone cement is greater than the speed at which the working gas is introduced.
10. Use of the magnesium-based hydrogen-rich bone cement according to any one of claims 1 to 5 in preparing bone defect repair materials.
Citation Information
Patent Citations
Magnesium slow-release bone cement with self-curing function and preparation method thereof
CN112043862A
Magnesium-based bone cement and its preparation method
CN114767932B
Cited By
A high-strength, injectable antioxidant paste material, its preparation method and application
CN122827877A
